2022
DOI: 10.1186/s12891-022-06028-8
|View full text |Cite
|
Sign up to set email alerts
|

Enthesitis-related arthritis: the clinical characteristics and factors related to MRI remission of sacroiliitis

Abstract: Background To describe the clinical characteristics and explore the factors related to the MRI remission of sacroiliitis in patients with enthesitis-related arthritis (ERA). Methods Patients with ERA from 2018–2022 in our medical center were retrospectively reviewed, which identified according to Pediatric Rheumatology International Trials Organization (PRINTO) criteria. Demographics, clinical characteristics, examinations, and treatments were desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Our result is more consistent with the French cohort, in which, 63% had axial symptoms and 47% developed sacroiliitis at a median time of 2.6 and 5.3 years respectively [ 9 ]. On the other hand, Li [ 17 ] found 88.5% ERA patients had sacroiliitis at diagnosis in a retrospective study done in Shanghai. Together, these results suggested that axial involvement might occur early in the disease course and more frequently than expected in children with ERA.…”
Section: Discussionmentioning
confidence: 99%
“…Our result is more consistent with the French cohort, in which, 63% had axial symptoms and 47% developed sacroiliitis at a median time of 2.6 and 5.3 years respectively [ 9 ]. On the other hand, Li [ 17 ] found 88.5% ERA patients had sacroiliitis at diagnosis in a retrospective study done in Shanghai. Together, these results suggested that axial involvement might occur early in the disease course and more frequently than expected in children with ERA.…”
Section: Discussionmentioning
confidence: 99%
“…Enthesitis is a predominant finding in juvenile spondyloarthritis and has been shown to affect 60-80% of JIA patients [11,50,51]. Characteristic locations include the following: the inferior pole of the patella, ischial tuberosity and various ligamentous and muscular attachments of the pelvis, and greater trochanter and calcaneus [11].…”
Section: Wb-mri In Jiamentioning
confidence: 99%
“…In seven categories, enthesitis-related arthritis (ERA) is the most common subtype in Southeast Asia affecting approximately 30% of all JIA and is associated with a poorer prognosis than other subtypes 3 4. Distinguishing clinical characteristics related to ERA include probable enthesitis and spinal involvement, and peripheral arthritis often presents as asymmetric arthritis of the lower extremities 5 6. These arthritis symptoms can lead to muscle weakness around the involved joints, limited range of joint motion, impaired aerobic fitness, fatigue, and resultant decreased function ability, reduced physical activity (PA), and an increase in the risk of fracture 7 8.…”
Section: Introductionmentioning
confidence: 99%